1999
DOI: 10.1017/s0950268899002186
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick and sharps injuries among health-care workers in Taiwan

Abstract: Sharps injuries are a major cause of transmission of hepatitis B and C viruses and human immunodeficiency virus in health-care workers. To determine the yearly incidence and causes of sharps injuries in health-care workers in Taiwan, we conducted a questionnaire survey in a total of 8645 health care workers, including physicians, nurses, laboratory technicians, and cleaners, from teaching hospitals of various sizes. The reported incidence of needlestick and other sharps injuries was 1.30 and 1.21 per person in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
41
2
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 14 publications
10
41
2
4
Order By: Relevance
“…These results are in agreement with those of Guo et al who found that 81.8% of all injuries and exposures were not reported by Taiwanese health care workers [12]. Reasons for not reporting injuries indicate a need for continued education about the risk of acquiring blood-borne pathogens from such injuries [14,15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in agreement with those of Guo et al who found that 81.8% of all injuries and exposures were not reported by Taiwanese health care workers [12]. Reasons for not reporting injuries indicate a need for continued education about the risk of acquiring blood-borne pathogens from such injuries [14,15].…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of needle-stick injuries among dentists in this study (66.5%) is less than that of health care workers in other studies. Chen et al reported that between 71% and 76% of Taiwanese nursing personnel had experienced needle-stick and sharps injuries [11] and Guo et al found that the prevalence of needle-stick injuries among Taiwanese health care workers ranged from 61% to 93% [12]. On the other hand, the frequency of needle-stick injuries in our study is higher than the 58% reported in the only regional study on such injuries in dental health care workers in Saudi Arabia [13].…”
Section: Discussioncontrasting
confidence: 73%
“…Items This research study consistent with the results carried out by Guo, Shiao, Chuang,( 2003), involving 550 medical students and residents during the 1989-1990 training year likewise reported a high prevalence of needle stick injuries (71%), and a higher frequency of injury (by a factor of 6) among surgical residents than among medical residents. In these two studies, rates of reporting needle stick injuries ranged from 9 to 19%, and a more recent survey of all types of providers from an Iowa medical organization found that 34% had reported their exposure to an employee health service.…”
Section: Level Of Awareness' Towards Policies Of Safety Measures Amonsupporting
confidence: 88%
“…They are a serious occupational health and safety concern globally for healthcare workers (HCWs) including the estimated 180,000 HCWs employed in the 420 accredited hospitals around Taiwan 1) . This preventable injury remains by far the most common cause of occupational transmission of bloodborne infection in HCWs in highly resourced countries 2,3) as well as Southeast Asia 4,5) , despite efforts to reduce PIs in recent years [6][7][8] . Many lowly and highly resourced healthcare systems have not yet introduced routine measurement of PIs and associated seroconversion rates.…”
mentioning
confidence: 99%